A finite-strain hyperviscoplastic model and undrained triaxial tests of peat - O'Kelly, Brendan C.; Nagel, T.; Zhang, Lin (My University, 2017)
This paper presents a finite-strain hyperviscoplastic constitutive model within a thermodynamically consistent framework for peat which was categorised as a material with both rate-dependent and thermodynamic equilibrium hysteresis based on the data reported in the literature. The model was implemented numerically using implicit time integration and verified against analytical solutions under simplified conditions. Experimental studies on the undrained relaxation and loading-unloading-reloading behaviour of an undisturbed fibrous peat were carried out to define the thermodynamic equilibrium state during deviatoric loading as a prerequisite for further modelling, to fit particularly those model parameters related to solid matrix properties, and to validate the proposed model under undrained conditions. This validation performed by comparison to experimental results showed that the hyperviscoplastic model could simulate undrained triaxial compression tests carried out at five different strain rates with loading/unloading relaxation steps.
Keywords: Viscoplasticity; Thermodynamically consistent; Finite strain; Constitutive model; Peat; Undrained triaxial tests; Smart & Sustainable Planet; Constitutive modelling; Constitutive modelling in geotechnical engineering; Environmental Geotechnics; Geotechnics; PEAT; PEAT SOILS; Soil Mechanics; Soil Mechanics & Foundations; geotechnical